2007
DOI: 10.1002/ccd.21296
|View full text |Cite
|
Sign up to set email alerts
|

Stenting for superior vena cava obstruction in pediatric heart transplant recipients

Abstract: SVC obstruction can be an important complication following heart transplantation, especially in infants with previous cavopulmonary anastomosis, undergoing heart transplant using bicaval technique. SVC obstruction can be safely and effectively treated using endovascular stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 6 publications
2
19
1
Order By: Relevance
“…Balloon dilation and/or stent implantation have been reported to be effective in SVC obstruction in several case series and small reports (13,(24)(25)(26)(27)(28)(29). In this study, we reported our experience with SVC intervention in patients previously supported with neonatal ECMO, a subset of patients who have not been specifically studied in prior reports.…”
Section: Transcatheter Treatment Of Svc Obstructionmentioning
confidence: 63%
“…Balloon dilation and/or stent implantation have been reported to be effective in SVC obstruction in several case series and small reports (13,(24)(25)(26)(27)(28)(29). In this study, we reported our experience with SVC intervention in patients previously supported with neonatal ECMO, a subset of patients who have not been specifically studied in prior reports.…”
Section: Transcatheter Treatment Of Svc Obstructionmentioning
confidence: 63%
“…23,24 There are few published reports on the incidence of SVC obstruction in transplant recipients and on the role of previous CPA as an independent risk factor for SVC obstruction after OHT. Although some reports highlight the association of SVC obstruction following CPA in both transplant 7,25 and nontransplant patients, other publications do not confirm this association. 27,28 …”
Section: Discussionmentioning
confidence: 94%
“…Superior vena cava (SVC) obstruction has emerged as a notable complication following OHT, particularly with the bicaval method of graft implantation. 13 It has been postulated that younger age at transplantation, donor—recipient caval mismatch, 4,5 and previous surgery involving the SVC, 6 and previous superior cavopulmonary anastomosis (CPA) 7 may be risk factors for posttransplant SVC obstruction. However, the incidence of SVC obstruction in pediatric heart transplant patients and the effect of pretransplant exposure to previous superior CPA or other types of non-CPA SVC surgeries remain unknown.…”
mentioning
confidence: 99%
“…[561][562][563][564][565][566][567][568][569][570][571][572][573] Although stents can be successfully used in infants aged , 1 year, the small vessel size increases the risk of thrombosis. 574 There are no studies assessing the role of anticoagulation or antiplatelet therapy to avoid stent occlusion in children.…”
Section: 40-242 Biologic and Mechanical Prosthetic Heart Valvesmentioning
confidence: 99%